Water Quality Monitoring System and Automatic Filter System Based on the Internet of Things - Nelvidawati; Firdaus (International Journal of Wireless And Multimedia Communications, 2024)
PDAM's peak usage of clean water means that water supply to customers often stops due to insufficient distribution of discharge and pressure. To overcome the problem of insufficient water flow, the community provides a water storage tank consisting of a ground water tank and an over head water tank. PDAM water received by the public through distribution pipes has the potential to be contaminated due to the entry of pollutants from repair activities and pipe leaks. These pollutants will accumulate in the tank, causing the water quality to decline and no longer comply with the established quality standards. To prevent accumulation of pollutants in the tank, before using it, the water should be filtered first. An automatic filtration system with monitoring of turbidity and water levels is a technology that can make people's work easier and the quality of the water used is in accordance with drinking water quality standards. Data obtained from turbidity and water level sensors can also be monitored via the IoT platform. The test results of the turbidity and water level sensors have a low error so that the designed tool can be used to monitor turbidity, water level and automatic filter systems. Sending data so that it can be displayed on IoT platforms such as Blynk has also been successfully created. From 10 attempts, the Water Level Sensor gave an average error of 0.78%.